Long-run consequences of natural disasters: Evidence from Tangshan - Guo Xu (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
Exploiting Tangshan 1976 - the deadliest earthquake in the 20th century - as a source of exogenous variation, we estimate the cohort-specific effects of a historical shock on contemporary socio-economic outcomes. While cohorts born after the earthquake were considerably larger, the adverse post-disaster conditions did not translate into lasting impacts on schooling and labour market outcomes. Cohorts at schooling age during the earthquake, however, exhibit considerably lower education levels today, particularly among the female. Despite lower education, there is no evidence for adverse labour market outcomes. We conduct extensive robustness checks and argue that the effect is causal.
Keywords: I20; J00; O18; 330; Environmental shock; earthquake; natural disaster; education; fertility